Mexico versus Canada: Stability benefits from making common currency with USD? - George M. Von Furstenberg (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
Using a de facto classification of exchange-rate regimes, this paper investigates how the volatility of PPP-GDP per person and per hour of work is associated with such regimes in Mexico and in Canada. It finds that, for Mexico unlike Canada, the macroeconomic volatility left is much greater during periods when the nominal exchange rate with USD changes appreciably than when it is quasi-pegged. However, Mexico cannot safely peg to USD except through formal USdollarization. Hence this finding suggests that the stability benefits of monetary union are greatest for emerging-market countries inside an economically integrating region and non-existent for financially highly advanced countries.
Keywords: 650